A strain-based fatigue damage model for naturally fractured marble subjected to freeze-thaw and uniaxial cyclic loads. (November 2021) - Wang, Y; Zhang, B; Li, B; Li, CH
The naturally fractured rock in the open pit slope is susceptible to irreversible damage caused by fatigue loads related to freeze-thaw weathering, blasting vibration, earthquakes and tramcar traffic. To ensure the safety of rock mass and reveal how natural fracture affects the damage modelling characteristics is of great concern. Hence, this work aims at investigating the fatigue damage evolution of rock from volumetric deformation caused by F-T and cyclic loads. The rock structural deterioration and damage accumulation were investigated as well as the stimulated natural fracture pattern. Results show the frost heaving force acted on natural fracture results in the rock volumetric changes. The damage variable expressed by volumetric strain presents a linear relationship with freeze-thaw cycles. In addition, the axial, lateral and volumetric strain of marble exposed to cyclic loads present a two-stage pattern, they first increase quickly and then get to steady and last for a long time. A new fatigue damage model was established by considering the freeze-thaw damage and mechanical damage simultaneously. The proposed coupling damage model can well describe rock damage accumulation. Moreover, the CT images further reveal the influence of the natural fracture on rock volumetric deformation and the final damage accumulation. It is suggested that the opening-mode natural fractures contribute a lot to rock freeze-thaw deformation and fatigue deformation.